An expert narrative review on the mechanisms and therapeutic potential of gut microbiota-derived metabolites in multi-organ crosstalk - Zhang, Yushu; Cao, Xuebin; Xiong, Shihong; Zhen, Wenqi; Yang, Yang; Gong, Na (Frontiers in Endocrinology, 2026)
BackgroundGut microbiota-derived metabolites—short-chain fatty acids (SCFAs), tryptophan derivatives, and uremic toxins—translocate systemically and mediate multi-organ crosstalk along the gut-kidney-heart-brain-endocrine axis, influencing host physiology and disease. However, integrated mechanistic insights remain limited.ObjectiveWe evaluated the effects of gut microbiota-derived metabolites (intervention) on inter-organ communication and disease outcomes in humans and model systems (population), compared to controls or standard care (comparison).MethodsWe conducted a narrative review of studies from PubMed, Cochrane Library, Embase, Web of Science, and ClinicalTrials.gov (2020–2025). We included randomized controlled trials, cohort studies, and mechanistic experiments. Two reviewers independently screened records using a standardized protocol; data synthesis employed narrative synthesis and random-effects meta-analysis where appropriate.Results41 included studies (n≈15,000 participants), SCFAs improved renal function (e.g., risk ratio [RR]=0.85 for composite outcomes, 95% CI: 0.72–0.98) with substantial heterogeneity (I²=68%). SCFAs conferred cardio protection and regulated neuroinflammation. Tryptophan metabolites showed dual roles in neuroprotection and metabolic dysfunction. Metabolites demonstrated diagnostic value (e.g., TMAO AUC = 0.87 for cardiovascular risk).ConclusionGut microbiota metabolites are pivotal in multi-organ crosstalk with moderate evidence certainty. They offer novel strategies for diagnosing and treating cardio-renal, metabolic, and neurological disorders, although individual variability and translational challenges persist.